Methodological foundations of the modern training system of skilled handballers - Tyshchenko, V. A. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose: to consider the direction of training handball team in the annual Ukrainian Superleague macrocycles game seasons in years 2006-2013.